Profile of Students' Scientific Literacy Skills on the ESD Theme in Renewable Energy Materials: A Case Study at SMA Negeri 15 Semarang, Indonesia - Hidayat, Arif Nur; Roshayanti, Fenny; Khoiri, Nur (Jurnal Penelitian Pembelajaran Fisika, 2024)
Science literacy is the ability to understand, communicate, and apply scientific knowledge to find solutions and to have sensitivity to self and the environment in making decisions based on scientific considerations. This study aims to acquire a profile of the science literacy skills of SMA Negeri 15 Semarang students. The study involved 606 students consisting of 290 students in the X class and 316 students in the XI class. Data was collected using the Education for Sustainable Development (ESD) science literacy instrument on Renewable Energy that refers to indicators developed by Gormally. ESD aims to empower individuals to act responsibly for the environment, economy, and society. The collected data is analyzed using descriptive statistics, i.e. average scores for each indicator, then the data is presented with a description. This study shows that the science literacy skills of students of SMA Negeri 15 Semarang need to be improved. The highest score is on making graphs accurately from data, while the lowest score is on making inferences, predictions, and conclusions based on quantitative data. Students' science literacy skills need to be improved through evaluation and practice of subjects involving science literature, learning with interactive media, and learning models that activate students.